LERCANIDIPINE, CALCIUM CHANNEL BLOCKER OF THE THIRD GENERATION: NEW POSSIBILITIES IN THE TREATMENT OF ARTERIAL HYPERTENSION - O. D. Ostroumova; M. L. Maksimov; I. I. Kopchenov (Рациональная фармакотерапия в кардиологии)
Classification, modes of action and clinical effects of calcium channel blockers are presented. Advantages of the third generation of dihydropyridine calcium channel blockers are considered. Clinical pharmacology, studies on the efficacy, safety and prevention of hypertensive complications with lercanidipine are detailed.